A non-linear hyperelastic foundation beam theory model for double cantilever beam tests with thick flexible adhesive. (February 2016) - Cabello, M.; Zurbitu, J.; Renart, J.; Turon, A.; Martínez, F.
Abstract: Flexible adhesive joints, with adhesives of very low elastic modulus and very large failure deformation, are of special interest in industrial applications. Nevertheless, there is a lack of effective models for predicting their behaviour for structural applications. Existing methods developed for stiff compressible adhesives are not able to accurately capture the nonlinearities present on a thick flexible bondline. This paper presents a new analytical model for the simulation of a flexible adhesive bonded joint in a double cantilever beam (DCB) setup. Using the concepts of elastic foundation beam theory and developing them for a more general non-linear hyperelastic foundation case, a semi-analytical model is proposed. The effectiveness of the model, with respect to other approaches shown in the literature, is compared against experimental results for Krafft's flexible adhesive SILKRON POLYMER H-100. The hyperelastic foundation model accurately predicts the load-displacement response of the adhesive.